The Approval of the Guardians of Children Resulted from the Marriage of Pre-marrital Pregnancy Women - Rahli Lamatande; Muh. Taufan; Akbar Akbar (State Institute for Islamic Studies Palu, 2019)
This research deals with the approval of the guardians of children resulted from the marriage of pre-married pregnant women (Case Study at the Office of Religious Affairs in Palasa District, Parigi Moutong, Central Sulawesi). This study uses qualitative research methods, through observation and in-depth interviews and document reviews. The data obtained were analyzed by data reduction techniques, data presentation, data verification, and drawing a conclusion. The results show that the procedure for implementing the guardian of a child resulted from the marriage of a pre-marital pregnant woman is carried out as a procedure for a general marriage. The first step is to register the marriage contract date within a period of 10 days, complete the requirements that have been set, namely in the form of N1. The guardian of children resulted from a pre-marital pregnant marriage can be approved if the requirements are fulfilled, the marriage principles, even though the act of adultery committed by his parents remains an act of adultery. When the requirements of the law of the state have been fulfilled, then there is no obstacle of his biological father to become the guardian of the child(daughter) resulted from pre-marital pregnant woman marriage. The legal basis for the implementation of the guardian of a child resulting from the marriage of a pre-marital pregnant woman is based on the regulations stated in the Law No. 1, 1974, (KHI) the articles 99 and 103.